Mechanical and Thermal Analysis of Classical Functionally Graded Coated Beam - Toudehdehghan A.; Mujibur Rahman M.; Tarlochan F. (EDP Sciences, 2023)
Beams and girders; Environmental engineering; Functionally graded materials; Thermoanalysis; Coated composites; Engineering applications; Functionally graded; Functionally graded material (FGM); Governing equations; Mechanical loads; Principle of virtual displacements; Thermo mechanical loads; Metal analysis